Factors related to self-care activities of patients with type 2 diabetes mellitus - Letícia Palota Eid; Sílvia Aparecida Dourado Leopoldino; Graziella Allana Serra Alves de Oliveira Oller; Daniele Alcalá Pompeo; Marlene Andrade Martins; Laís Palota Balderrama Gueroni (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To verify self-care activities of patients with type 2 diabetes mellitus and to analyze the relationship with sociodemographic and clinical variables. Method: A cross-sectional study was performed of 149 people using the Diabetes Self-Care Activities Questionnaire. Results: Of the 15 self-care activities analyzed, appropriate behavior was observed for aspects related to medication use and inadequate for fruit/vegetable consumption, blood sugar testing and physical exercise. The correct use of medications was correlated to marital status. Regarding inadequate behaviors, there were associations of fruit/vegetable consumption with skin color and place of residence and blood sugar testing with marital status and inverse correlations of physical exercise with systolic blood pressure, pulse pressure, waist circumference and postprandial glycemia. Conclusion: The results of this research contribute by strengthening the line of care in chronic diseases and assist in divulging the importance of supported self-care. Implications for practice: The findings of this research provided information relevant to the planning of care.